Osteopontin but not osteonectin favors the metastatic growth of pancreatic cancer cell lines - Zhivkova-Galunska, Maria; Adwan, Hassan; Eyol, Ergül; Kleeff, Jörg H.; Kolb, Armin; Bergmann, Frank; Berger, Martin R. (Cancer biology & therapy, 2010)
Pancreatic ductal adenocarcinoma (PDAC) is the fourth leading cause of cancer- related death in Western countries and among the malignancies with the worst prognosis. Osteonectin and osteopontin, two proteins of the extracellular matrix, have been found to be up-regulated in PDAC. In the present study the expression of osteopontin mRNA as determined in a panel of 14 human pancreatic cancer cell lines was significantly related to the growth these cell lines in the liver of nude rats (p=0.001) whereas osteonectin showed a trend of being negatively related to pancreatic cancer cell growth in vivo (p=0.10). In an in vitro co-culture model of human Suit2-007 and rat AsML PDAC cells with rat hepatocytes, a clearly increased expression of OPN mRNA was found in the tumor cells. In addition both, down-regulation of osteopontin with specific antisense oligonucleotides and treatment with exogenous rh-osteonectin were associated with reduced cell proliferation. In accordance with the latter finding down-regulation of osteonectin was coupled with increased proliferation. This evidence supports a protumorigenic role of osteopontin and points to an anti-tumorigenic role of osteonectin in PDAC.
Gesehen am 12.03.2024